The impact of external cash flows on economic growth in Sudan During the period (1990-2014) - د. صلاح محمد ابراهيم أحمد; محمد مسعود محمد ادريس (White Nile Journal for Studies and Research, 2016)
The study aimed to measure the impact of external cash flows that are in foreign direct investment and foreign debt on economic growth in the Sudan during the period (1990-2014). The study represented a problem in the main question: What is the impact of foreign direct investment and foreign debt on economic growth in Sudan? The study assumed that foreign direct investment affect economic growth in the Sudan and that the external debt affect the economic growth in Sudan. The study used the theoretical side inductive by extrapolating research studies and books, local and foreign journals. On the practical side, use descriptive and analytical approach. The most important findings of the study: a positive relationship between FDI and economic growth in Sudan, where the increase in foreign investment leads to an improvement of per capita income and there is a direct correlation between external debt and economic growth in Sudan that is, increasing foreign debt and directing them towards production would increase economic growth, the study also concluded that pure foreign flows affect economic growth by 20%. The study recommends the need to facilitate administrative procedures and make them take place in a single window to save time and effort and thus increase foreign direct investment flows, which in turn is reflected in the increase in economic growth rates in Sudan, and should be amended and the review of legislation and laws and investment in order to increase foreign direct investment flows, which in turn is reflected in the increasing rates of growth economic Sudan and the need to give more facilities foreign investor to take advantage of local financial institutions You should take advantage of the external debt in the growth and economic development in the country projects, in addition to direct them to productive projects rather than the money-losing projects because it exacerbates the debt and adversely affect the economic situation must also be public debt management more efficient and directed towards investment and productive projects for export.